2009
DOI: 10.1021/ja908379q
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Narrowly Dispersed Brush Copolymers and Study of Their Assemblies: The Importance of Side Chain Arrangement

Abstract: Efficient, one-pot preparation of synthetically challenging, high molecular weight (MW), narrowly dispersed brush block copolymers and random copolymers in high conversions was achieved by ring-opening metathesis (co)polymerization (ROMP) of various macromonomers (MMs) using the highly active, fast-initiating ruthenium olefin metathesis catalyst (H2IMes)(pyr)2(Cl)2RuCHPh. A series of random and block copolymers were prepared from a pair of MMs containing polylactide (PLA) and poly(n-butyl acrylate) (PnBA) side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
582
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 460 publications
(616 citation statements)
references
References 61 publications
30
582
1
3
Order By: Relevance
“…All samples prepared were self-assembled in the melt to form 14.3 nm lamellar domains, independent of backbone DP. These random bottlebrush copolymers also exhibited a T ODT dependent on the side-chain length and independent of backbone length 33 .…”
Section: Bulk and Thin Film Self-assembly Of Bottlebrush Block Copolymentioning
confidence: 89%
See 2 more Smart Citations
“…All samples prepared were self-assembled in the melt to form 14.3 nm lamellar domains, independent of backbone DP. These random bottlebrush copolymers also exhibited a T ODT dependent on the side-chain length and independent of backbone length 33 .…”
Section: Bulk and Thin Film Self-assembly Of Bottlebrush Block Copolymentioning
confidence: 89%
“…Subsequently, in 2008, Xia and Grubbs et al reported the use of a highly-active ruthenium catalyst for achieving improved control over bottlebrush molecular weight and molecular weight dispersity 22,33 . The reactivity of norbornenyl macromonomers in ROMP is sufficient for achieving high macromonomer conversions for a range of concentrations and macromonomer molecular weights, enabling the preparation of bottlebrush polymers with systematically varying backbone and side-chain lengths.…”
Section: Synthesis Of Bottlebrush Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…[49][50][51][52] We targeted poly(D,L-lactide)-b-polystyrene (PLA-b-PS) graft diblock polymers to permit comparisons with brush PLA-b-PS systems previously investigated in the context of self-assembly. [21][22][23][24][25] All polymerizations were carried out in CH2Cl2 at room temperature under an inert atmosphere. To vary the grafting density (Figure 1), the first block was synthesized by copolymerizing a PLA macromonomer (Mn = 3230 g/mol) with a discrete co-monomer (i.e., diluent), DME (endo,exonorbornenyl dimethyl ester, Mn = 210 g/mol).…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] However, bottlebrush block polymers display much larger scaling exponents ( = 0.8-0.9), [21][22][23][24] consistent with extended backbone conformations. Steric repulsion between the densely grafted side chains imparts a certain bending rigidity to the backbone, which can be modeled as a wormlike chain.…”
mentioning
confidence: 99%